2023
DOI: 10.1002/batt.202200454
|View full text |Cite
|
Sign up to set email alerts
|

Research in Electrochromic Supercapacitor – A Focused Review

Abstract: Attributed to its high safety and fast charging capabilities, supercapacitor is one of the most widely active research fields in the energy storage for last several decades. Recently, with the significant advances on the internet‐of‐things (IoT) technologies as well as growing market demands for wearable electronics, not only the electrochemical performance but also visual aspects of the devices become increasingly important. In this aspect, electrochromic supercapacitor has garnered significant attention in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Electrochromic materials (such as polyaniline (PANI), tungsten trioxide (WO 3 ), and Prussian blue), as visualized signal display screens, have the advantages of reversible color change, long cycle life, and rapid signal response. Composed of positive and negative electrochromic materials and an electrolyte layer, an electrochromic supercapacitor (ESC) produces reversible color changes under different voltages. , Therefore, the ESC, as a signal display screen, has excellent cycling stability and reusability. For example, the ESC was constructed based on the matching color changes for WO 3 and PANI films under different ion-storage states .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochromic materials (such as polyaniline (PANI), tungsten trioxide (WO 3 ), and Prussian blue), as visualized signal display screens, have the advantages of reversible color change, long cycle life, and rapid signal response. Composed of positive and negative electrochromic materials and an electrolyte layer, an electrochromic supercapacitor (ESC) produces reversible color changes under different voltages. , Therefore, the ESC, as a signal display screen, has excellent cycling stability and reusability. For example, the ESC was constructed based on the matching color changes for WO 3 and PANI films under different ion-storage states .…”
Section: Introductionmentioning
confidence: 99%
“…17−20 Composed of positive and negative electrochromic materials and an electrolyte layer, an electrochromic supercapacitor (ESC) produces reversible color changes under different voltages. 21,22 Therefore, the ESC, as a signal display screen, has excellent cycling stability and reusability. For example, the ESC was constructed based on the matching color changes for WO 3 and PANI films under different ion-storage states.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the thriving electronic industry in the past few decades, the development of novel optoelectronic materials has rapidly progressed. Electrochromic (EC) materials have become attractive due to the reversible color change under electrochemical oxidation and reduction. With the controllable optical behaviors and energy storage potential, EC materials reveal promising applications in several regions, including transparent displays, antiglare mirrors, smart windows, adaptive camouflage, supercapacitors, and batteries. Triphenylamine (TPA) is a representative EC material with high optical contrast between the transparent neutral state and the colored oxidation state. TPA-derived polymers have become spotlights due to their excellent electrochemical and EC characteristics and tunable structures. The imperative features of an ideal EC material include a low oxidation voltage, fast response speed, high optical contrast, coloration efficiency, and good long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, thermodynamic analysis performed by means of density functional theory (DFT) calculations proved that this cation exchange and proton intercalation process is not feasible at battery operation conditions [27] . Other experimental studies explored the electrochemical performance of LCO as a cathode material for reversible Li intercalation using a highly concentrated lithium nitrate and lithium sulphate aqueous solutions, [28–30] revealing that LCO showed the same pattern observed using non‐aqueous electrolytes with very low degradation, mainly related with surface effects due to vacancy [31] and defects generation. The formation of lithium hydroxide and cobalt hydroxide on the surface of the material is one of the common drawbacks to use LCO as the cathode for aqueous LIBs (ALiBs), since these hydroxides can compromise the performance of the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of lithium hydroxide and cobalt hydroxide on the surface of the material is one of the common drawbacks to use LCO as the cathode for aqueous LIBs (ALiBs), since these hydroxides can compromise the performance of the cathode. However, during the reverse Li intercalation reaction, only the formation of Co 3 O 4 spinel planes were detected at surface level, without a decay in the battery performance [31] . Furthermore, it was reported that the use of additives helps to stabilize LCO at high voltages [32] …”
Section: Introductionmentioning
confidence: 99%